2013
DOI: 10.1002/alr.21226
|View full text |Cite
|
Sign up to set email alerts
|

Interferon gamma causes olfactory dysfunction without concomitant neuroepithelial damage

Abstract: Introduction Olfactory loss is a debilitating symptom of chronic rhinosinusitis (CRS). The pathophysiology of inflammatory olfactory dysfunction likely involves both conductive and sensorineural components. To study the interaction of CRS-associated inflammatory cytokines with the olfactory epithelium, a transgenic mouse model was developed that allows temporally-controlled local gene expression. Interferon-gamma (IFN-γ) is a prototypical Th1 cytokine linked to non-polypoid CRS, as well as sinonasal viral and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…These effects have been previously reported for an array of cytokines that include tumor necrosis factor α (TNF‐α), IL‐6, and interferon γ (IFN‐γ) . The potential adverse effects of TNF‐α and IFN‐γ on olfactory neuron function and/or survival have been confirmed in recent animal studies . Likewise, Henkin et al .…”
Section: Discussionmentioning
confidence: 64%
“…These effects have been previously reported for an array of cytokines that include tumor necrosis factor α (TNF‐α), IL‐6, and interferon γ (IFN‐γ) . The potential adverse effects of TNF‐α and IFN‐γ on olfactory neuron function and/or survival have been confirmed in recent animal studies . Likewise, Henkin et al .…”
Section: Discussionmentioning
confidence: 64%
“…In previous studies from mice models, it is reported that TNF-a inhibits olfactory regeneration [32] and directly causes physiologic dysfunction of olfactory neurons [29]. Also, chronic IFN-c expressions in the mouse have been caused olfactory dysfunction [20]. On the other hand, elevated IL-6 (as a pro-inflammatory cytokine) levels were found in plasma, saliva, and nasal mucus in patients with hyposmia recently [9].…”
Section: Discussionmentioning
confidence: 99%
“…Several cytokines have neurotoxic potential, and it is conceivable that the olfactory dysfunction in CRS patients may be mediated in part by their effects on olfactory neuronal cell function, apoptosis, differentiation, and proliferation. Recent evidence from transgenic mouse models have supported this olfactory inflammation hypothesis, with local overexpression of proinflammatory cytokines such as tumor necrosis factor‐α (TNF‐α) and interferon‐γ, resulting in inhibition of olfactory neuron function, turnover, or survival . Likewise, a recent study in patients with CRS found that quantitative olfactory function may be inversely associated with olfactory mucus levels of interleukin (IL)‐5 …”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence from transgenic mouse models have supported this olfactory inflammation hypothesis, with local overexpression of proinflammatory cytokines such as tumor necrosis factor-a (TNF-a) and interferon-c, resulting in inhibition of olfactory neuron function, turnover, or survival. [20][21][22][23] Likewise, a recent study in patients with CRS found that quantitative olfactory function may be inversely associated with olfactory mucus levels of interleukin (IL)-5. 24 Despite the putative importance of proinflammatory cytokines in olfactory function, studies to clarify the role of cytokines in human olfactory tissue have been limited.…”
Section: Introductionmentioning
confidence: 99%